Pembelajaran Menulis Puisi sebagai Sarana Menumbuhkan Empati dan Nilai Kemanusiaan Siswa - Anita Candra Dewi (FKIP UNSULTRA, 2025)
Learning to write poetry has significant potential in shaping students' character, particularly in fostering empathy and humanitarian values. Poetry is not only a means of aesthetic expression but also a medium for self-reflection on social, emotional, and moral experiences. This literature review aims to analyze the role of learning to write poetry in fostering empathy and humanitarian values ​​in elementary school students. The research was conducted by reviewing various national and international scientific articles published between 2018 and 2025. The results indicate that learning to write poetry can increase students' emotional sensitivity to the social environment, strengthen their ability to understand others' feelings, and foster moral awareness through reflective and creative processes. Effective learning strategies in this context include appreciative, reflective, and contextual approaches supported by digital media relevant to children's worlds. Through poetry writing activities, students learn to interpret personal and social experiences into meaningful literary works. This study confirms that learning to write poetry has strategic value in character education, particularly in shaping an empathetic, cultured, and humane generation.